The Failure to Recognize Continuing Harm: Post-Separation Domestic Abuse in Child Contact Cases - Walsh, Kieran (Violence against women, 2025)
This article presents findings from a case file review of post-separation parenting cases in England and Wales. It first outlines that jurisdiction's legal framework relevant to these cases, before providing an overview of the findings relating to the profile of the cases and their outcomes. It then describes the types of abuse most frequently encountered in these cases, and examines the attitude of the courts to post-separation abuse by looking at both interim and final court orders. The study finds that key legal provisions governing these cases are not being followed, with little understanding shown for the nature of post-separation abuse.